Pengaruh Financial Distress dan Corporate Social Resposibility terhadap Konservatisme Akuntansi - Muhammad Nur Caniago; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2023)
The financial report is a description of the company's performance. This study aims to determine the effect of financial distress and corporate social responsibility on accounting conservatism. Manufacturing companies listed on the Indonesia Stock Exchange are the population in this study with the 2017-2019 research period. The number of samples analyzed were 34 companies. Samples were taken by purposive sampling method. The analysis technique used is multiple linear analysis technique. The results show that financial distress has a positive effect on accounting conservatism, corporate social responsibility has no effect on accounting conservatism. Suggestions for further research are expected to increase the number of research samples and years of observation, and also to use other variables that can be used to measure the level of accounting conservatism.